2007
DOI: 10.1021/cm062831v
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Transistors Based on Alkylphenyl Quaterthiophenes:  Structure and Electrical Transport Properties

Abstract: 3) were grown by vacuum deposition on thermally grown SiO 2 substrates and characterized in a thin film transistor (TFT) configuration. Atomic force microscopy and specular (θ-2θ) X-ray diffraction (XRD) revealed films with small, crystalline grains, in which the oligothiophenes were oriented "end-on" with respect to the SiO 2 substrate. Interplanar spacing increased (1 ) 28.0 Å, 2 ) 29.5 Å, 3 ) 37.7 Å), consistent with increasing alkyl tail length. Grazing incidence X-ray diffraction (GIXD) of the films (ca. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…The large conductance enhancement reveals that the DQI effects will occur in the most probable configuration as the planar conjugation is enlarged, which is consistent with previous organic thin-film transistor studies with thiophene derivatives showing the high conjugation degree leads to better field-effect response and carrier mobilities. We further investigated the conductance evolution of the linear-chain structural TPCOs with different thiophene numbers and found that the conductance enhancement among them is negligible (Figure S11). Similar results have also been found in the thin-film transistors, , suggesting that the chain length of thiophene units has little effect on the intrinsic field-effect response of the π-stacked TPCOs at the single-molecule level.…”
Section: Resultssupporting
confidence: 80%
“…The large conductance enhancement reveals that the DQI effects will occur in the most probable configuration as the planar conjugation is enlarged, which is consistent with previous organic thin-film transistor studies with thiophene derivatives showing the high conjugation degree leads to better field-effect response and carrier mobilities. We further investigated the conductance evolution of the linear-chain structural TPCOs with different thiophene numbers and found that the conductance enhancement among them is negligible (Figure S11). Similar results have also been found in the thin-film transistors, , suggesting that the chain length of thiophene units has little effect on the intrinsic field-effect response of the π-stacked TPCOs at the single-molecule level.…”
Section: Resultssupporting
confidence: 80%
“…Frisbie et al prepared a series of alkylphenyl-substituted oligothiophenes 2.57e−g by Stille-type reaction of 2-bromo-5-(4-alkylphenyl)thiophene and corresponding distannylated moieties. , All compounds showed p-type transport character and hole mobilities in the range of 0.03 cm 2 V −1 s −1 and improved I on / I off ratios approaching a record 10 9 for 2.57f ( n = 2) at room temperature. These findings revealed that increasing alkyl chains do not improve the molecular ordering; however, the addition of phenyl groups greatly improves the on/off ratio in OFETs.…”
Section: Functionalized Linear Oligothiophenesmentioning
confidence: 99%
“…However, at the same time it dramatically reduces the molecule’s solubility, limiting its potential for application in solution processable large area electronics. Only a few examples of oligomers with six or more conjugated thiophene rings with sufficient solubility are described in the literature. , Thus, the search for a reasonable compromise between the electronic properties and the ease of processing is very important. …”
mentioning
confidence: 99%